Non-destructive evaluation by terahertz spectroscopy for penetration of acid solutions into epoxy resin - M. Kusano; M. Kubouchi; D. S. Bulgarevich; M. Shiwa (eXPRESS Polymer Letters, 2016)
Epoxy resins are used as high-performance thermosetting linings to protect substrates under corrosive environments. However, in a severe corrosive chemical solution, such protective layers may degrade with long time due to penetrations of solvent and solute molecules into resin network. In this regard, the terahertz time-domain spectroscopy (THz-TDS) is a promising tool for non-destructive evaluation of the penetrant amounts due to high transparency of such plastic materials and high sensitivity to the molecular vibrations in terahertz spectral range. In this work, the complex refractive indexes n and κ of epoxy specimens were measured after immersion into sulfuric acid solutions and compared with penetrated mass fractions of water and acid ions. It was found that n and κ depended linearly with water and sulfuric acid mass fraction in specimens, and κ of sulfuric acid immersed specimens was lager at higher frequency. While the calculated Δκ agreed well with THz-TDS measurement by THz-TDS, the calculated Δn was higher than the measurement. The difference may be attributed to the water and sulfuric states in the specimen.